Zanthoxylum ailanthoides Suppresses Oleic Acid-Induced Lipid Accumulation through an Activation of LKB1/AMPK Pathway in HepG2 Cells. (8th January 2018) - Kwon, Eun-Bin; Kang, Myung-Ji; Kim, Soo-Yeon; Lee, Yong-Moon; Lee, Mi-Kyeong; Yuk, Heung Joo; Ryu, Hyung Won; Lee, Su Ui; Oh, Sei-Ryang; Moon, Dong-Oh; Lee, Hyun-Sun; Kim, Mun-Ock
Abstract : Zanthoxylum ailanthoides (ZA) has been used as folk medicines in East Asian and recently reported to have several bioactivity; however, the studies of ZA on the regulation of triacylglycerol (TG) biosynthesis have not been elucidated yet. In this study, we examined whether the methanol extract of ZA (ZA-M) could reduce oleic acid- (OA-) induced intracellular lipid accumulation and confirmed its mode of action in HepG2 cells. ZA-M was shown to promote the phosphorylation of AMPK and its upstream LKB1, followed by reduction of lipogenic gene expressions. As a result, treatment of ZA-M blocked de novo TG biosynthesis and subsequently mitigated intracellular neutral lipid accumulation in HepG2 cells. ZA-M also inhibited OA-induced production of reactive oxygen species (ROS) and TNF- α, suggesting that ZA-M possess the anti-inflammatory feature in fatty acid over accumulated condition. Taken together, these results suggest that ZA-M attenuates OA-induced lipid accumulation and inflammation through the activation of LKB1/AMPK signaling pathway in HepG2 cells.